GEOLOGI DAN POLA SEBARAN BATUBARA FORMASI SINAMAR DI PT KUANSING INTI MAKMUR, KABUPATEN BUNGO - Rakhmatul Arafat; Dino Kurnia Putra; Dedy Antony (JGE (Jurnal Geofisika Eksplorasi), 2026)
Coal is a vital energy resource for Indonesia, particularly within the Jambi Province. Several coal bearing formations in the region, such as the Muara Enim and Sinamar Formations, are known to host high-quality coal. Despite this potential, geological research on the Sinamar Formation remains limited compared to the Muara Enim Formation. This study is located within the Mining Business License area of PT Kuansing Inti Makmur, specifically in Tanjung Belit Village, Jujuhan District, Bungo Regency, Jambi Province. The objective of this research is to characterize the geological conditions and coal distribution patterns to support future mine planning. The methodology includes field observations through geological mapping, rock sampling, and petrographic analysis, complemented by indirect observations via subsurface modeling using Minescape software based on company borehole data. The results indicate that the morphology of the study area consists of Structural Hills (S1) and anthropogenic landforms, including Mine Excavation Unit (A1) and Waste Dump Unit (A2). Stratigraphically, the area is composed of the Sinamar Conglomerate Unit with andesite fragments, the Sinamar Sandstone Unit, and the Sinamar Claystone Unit. A Left Normal Slip Fault with a general northwest–southeast orientation was identified. The coal distribution pattern consists of three seams (Seams A, B, and C) with thicknesses ranging from 1.5 to 6 meters. In conclusion, the coal layers in this area exhibit a strike of N 293° E – N 305° E with an average dip of 23°–30°.